Osmanlı Döneminde Şam’da Bir Mahalle: Şehîd Nureddin Mahallesi - Samıkıran, Oğuzhan (Fırat University, 2014)
Şehir surları dâhilinde yer alan Şehîd Nureddin Mahallesi, ismini Mahmud Nureddin Zengî’den almıştır. Sultan Nureddin tarafından idarî, askerî, iktisadî, dinî ve kültürel alanda gerçekleştirilen imâr faaliyetleri, mahallenin şekillenmesinde önemli bir rol oynamıştır. 1617 ve 1700 yılları arasında mahalle, sayısı 9 ile 19 arasında değişen sokağı ihtiva etmekteydi. Şehîd Nureddin Mahallesi 1617’de 74,5; 1656-1657’de 47,5; 1672-1673’te 45,5; 1673-1674’de ise 43,5 ‘avârız-hâne sayısına sahipti. 1675-1676 yıllarında ise mahallede toplam 724 beytin mevcut olduğu tespit edilmiştir

The Quarter of Şehîd Nureddin which stands inside the city walls has taken its name from Mahmud Nureddin Zengî. The constuction activities which were performed by Sultan Nureddin in administrative, military, economic, religious and cultural areas have played an important role in the formation of the quarter. The quarter contained ‘‘sokak’’ numbers ranging from 9 to 19 between the years of 1617 and 1700. The Quarter of Şehîd Nureddin had 74,5 ‘avârız-hânes at 1617; 47,5 ‘avârız-hânes at 1656-1657; 45,5 ‘avârız-hânes at 1672-1673; 43,5 ‘avârız-hânes at 1673-1674. At the years of 1675-1676 it was detected that there were724 beyts in total in the quarter
A Quarter in Damascus in the Ottoman Period: the Quarter of Şehîd Nureddin